Personality Traits and Cognitive Ability in Political Selection - Jokela, Markus; Meriläinen, Jaakko; Tukiainen, Janne; von Schoultz, Åsa (Oxford University Press, 2026)
A vast scholarship questions whether voters are sufficiently informed to act in their best interest at the polling booth, which may also have implications for the quality of political representation. In this study, we examine cognitive and non-cognitive ability tests conducted on (male) military conscripts by the Finnish Defense Forces and compare local and national election candidates nominated by political parties and representatives elected by voters with each other and the general population. We show that non-elected candidates fare better in the tests than the population, on average, and elected politicians demonstrate even higher levels of ability. Local politicians’ cognitive and non-cognitive skills are on par with individuals who work in high-skill occupations or have at least an undergraduate degree, and national politicians are even better. Our findings suggest that, despite the complex decision-making environment inherent in voter-oriented systems, a political class that is more competent, motivated, and honest than the general population emerges. We further discuss the scope for positive political selection of women, show that there is no evident trade-off between politician quality and descriptive representation, and present evidence on the mechanisms for and the policy effects of positive selection.